On the status of Microrhopala arizonica Schaeffer (Coleoptera: Chrysomelidae: Cassidinae: Chalepini) - Riley, Edward G. (Zootaxa, 2019)
The specific status of Microrhopala arizonica Schaeffer 1906 is restored by its removal from synonymy with Pentispa suturalis (Baly 1885). The type specimens of Chalepus suturalis Baly 1885 and Microrhopala arizonica Schaeffer 1906 were studied together with numerous additional specimens. Lectotypes are designated for both names to stabilize their applications. Confusion surrounding the name Microrhopala suturalis Weise 1905 is discussed. Following currently held generic concepts, M. arizonica is a member of the genus Microrhopala Chevrolat 1836 and not Pentispa Chapuis 1875. A brief summary of the history of these names is presented, and the diagnostic characters for separating the two species as well as those that distinguish the genera Microrhopala and Pentsipa are discussed.